2008
DOI: 10.1002/eat.20517
|View full text |Cite
|
Sign up to set email alerts
|

What's love got to do with it? Family cohesion and healthy eating behaviors in adolescent girls

Abstract: Objective: To examine the association between family cohesion and behaviors linked to health or overweight in adolescents.Method: Cross-sectional analyses of family cohesion and eating behaviors of 2,379 girls (followed from ages 9-19) who participated in the National Heart, Lung, and Blood Institute Growth and Health Study (NGHS). Height and weight measurements were obtained on an annual basis. Family cohesion was measured by the Family Adaptability and Cohesion Evaluation Scale (FACES) III. Food diaries were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 48 publications
8
63
1
2
Order By: Relevance
“…In our study, the only socio-economic variable that was associated with breakfast consumption was maternal education level; adolescents whose mothers had a high education level were more likely to be breakfast consumers compared with adolescents whose mothers had a low/medium education level. Similar results have been found in Norway (15) and the USA (30,31) . Additionally, our study shows that adolescents whose mothers had a high education level were more likely to consume a breakfast of higher quality, to consume the target food groups and were less likely to consume 'soft drinks' for breakfast.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the only socio-economic variable that was associated with breakfast consumption was maternal education level; adolescents whose mothers had a high education level were more likely to be breakfast consumers compared with adolescents whose mothers had a low/medium education level. Similar results have been found in Norway (15) and the USA (30,31) . Additionally, our study shows that adolescents whose mothers had a high education level were more likely to consume a breakfast of higher quality, to consume the target food groups and were less likely to consume 'soft drinks' for breakfast.…”
Section: Discussionsupporting
confidence: 88%
“…Unemployment and parent's educational level did not have a relation with the rate of breakfast consumption by children. Franko 34 in a ten-year study showed that breakfast consumption in family is accompanied with some changes with the living style girls.…”
Section: Discussionmentioning
confidence: 99%
“…Low family functioning is associated with health outcomes and health behaviours such as overweight (20,21) , sedentary behaviour (20) and low intake of fruit and vegetables (20,22,23) . Franco et al suggested that adolescents who experience a high level of family communication and support are more susceptible to parents' advice about breakfast consumption (24) . A recent study by Berge et al found that high family functioning (communication, closeness, problem solving, behavioural control) among US adolescents (mean age of 14·4 years) was associated with daily breakfast consumption (20) .…”
mentioning
confidence: 99%